1987
DOI: 10.1093/clinchem/33.8.1343
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin secretion in humans assessed by measuring its metabolite, 6-sulfatoxymelatonin.

Abstract: Comparing a direct radioimmunoassay for 6-sulfatoxymelatonin (aMT6s) with an established gas chromatographic/mass spectrometric method for 6-hydroxymelatonin, we found a good correlation r = 0.94 (P less than 0.001, n = 100). aMT6s was stable, both in urine and plasma samples, without preservative, for at least two years at -20 degrees C and for five days at room temperature. Urinary excretion of aMT6s showed considerable inter-individual differences; however, the aMT6s excretion of any one individual was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
3

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(63 citation statements)
references
References 8 publications
5
55
0
3
Order By: Relevance
“…Of these serotonin availability would be the most likely mechanism underlying the acute effect of fluvoxamine. In previous studies of healthy untreated subjects, urinary aMT6s concentrations have proved to be a reliable reflection, both qualitative and quantitative, of plasma melatonin levels [4,30]. However, in view of our findings of a lack of correlation between plasma melatonin and urinary aMT6s concentrations following fluvoxamine treatment, the possibility that fluvoxamine inhibits the hepatic metabolism of melatonin and therefore delays its clearance from the plasma must be considered.…”
Section: Discussionmentioning
confidence: 61%
“…Of these serotonin availability would be the most likely mechanism underlying the acute effect of fluvoxamine. In previous studies of healthy untreated subjects, urinary aMT6s concentrations have proved to be a reliable reflection, both qualitative and quantitative, of plasma melatonin levels [4,30]. However, in view of our findings of a lack of correlation between plasma melatonin and urinary aMT6s concentrations following fluvoxamine treatment, the possibility that fluvoxamine inhibits the hepatic metabolism of melatonin and therefore delays its clearance from the plasma must be considered.…”
Section: Discussionmentioning
confidence: 61%
“…We have therefore examined the relationship between size at birth and overnight 6-sulphatoxymelatonin excretion in a population-based study of men and women, aged 20, whose birth measurements had been recorded in detail. The urinary melatonin metabolite, 6-sulphatoxymelatonin is a reliable indicator of melatonin production [Fellenberg et al, 1980;Bojkowski et al, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating melatonin is predominantly hydroxylated and conjugated with sulfate in the liver to form 6-sulfatoxymelatonin (aMT6s), which is excreted in high amounts in urine and has been used as an indicator of circulating melatonin [7][8][9][10]. Previous studies have found correlations between urinary melatonin excretion, especially nocturnal excretion, and circulating melatonin in plasma [5,[11][12][13][14][15][16] or in serum [17,18]. Urinary aMT6s has also been found to correlate with melatonin in plasma [11-13, 15, 16, 19, 20] or in serum [18,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although several studies have concentrated on measuring melatonin secretion during the entire 24-hr period [13,14,[19][20][21][22][23][24], the main tendency has been to follow only nocturnal melatonin secretion. The excretion of aMT6s has been used as a measure of melatonin secretion in many earlier studies [11-16, 18-22, 24, 25], but that of urinary melatonin in only few [5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%